PERNIKAHAN DINI PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF (STUDY KASUS PENGADILAN AGAMA KABUPATEN MALANG) - Muhammd Zulqifli Akbar; Ach Faisol; Ibnu Jazari (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
Early marriage has become a social problem due to promiscuity, way of life and culture in community groups. This problem is still attached to the majority of the people of Malang Regency. The purpose of this research is to clarify the issue of early marriage and positive law, as well as Islamic views on early marriage. This study uses descriptive qualitative research methods. This research uses descriptive qualitative research method. Data collection is done by interview and documentation techniques. The results of the study indicate that early marriage in Malang Regency is classified as